Given the Quadratic Equation:
![x^2-9x-36=0](https://img.qammunity.org/2023/formulas/mathematics/college/qf1myv5fwimkknw3btkuszuddarmn1jcow.png)
You need to remember that the Zero Product Property states that if:
![ab=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/t0sb62dzrz8izmiw1nnkz1z4asxh5c0l4l.png)
Then:
![a=0\text{ }or\text{ }b=0](https://img.qammunity.org/2023/formulas/mathematics/college/csvmg3nqp8ukxwwg0dhj5g4fojgsbm51di.png)
In this case, you can factor the given equation by finding two numbers whose sum is -9 and whose product is -36. These numbers are 3 and -12. Then:
![(x+3)(x-12)=0](https://img.qammunity.org/2023/formulas/mathematics/college/ua6t5t6a7trpsn4940ra9mirb12px8nmv6.png)
Based on the Zero Product Property, you know that:
![(x+3)=0\text{ }or\text{ }(x-12)=0](https://img.qammunity.org/2023/formulas/mathematics/college/gn9b0uj253ymr2srtsgtoivpsgwv0of626.png)
Then, by solving each part by "x", you get:
![x=-3\text{ }or\text{ }x=12](https://img.qammunity.org/2023/formulas/mathematics/college/xlk01ygfmxuzkds6nk1mgrnowlr3gjtmi1.png)
Hence, the answer is:
![x=-3\text{ }or\text{ }x=12](https://img.qammunity.org/2023/formulas/mathematics/college/xlk01ygfmxuzkds6nk1mgrnowlr3gjtmi1.png)